Proceedings of the 3rd International Conference on Material, Mechanical and Manufacturing Engineering 2015
DOI: 10.2991/ic3me-15.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Activity of Banana (Musa nana Lour.) Peel and Its Active Ingredients in Alloxan-Induced Diabetic Mice

Abstract: Abstract. Previous studies have found that banana flowers, leaves, pseudostems, roots, infructescence stalks, and peels (M. paradisiacal (Linn.)) have antihyperglycemic effect. The banana peel (Musa nana Lour.) might have the antihyperglycemic activity, its antihyperglycemic activity and active ingredients remain to be elucidated. In this paper, fresh banana peel was sequential extraction using solvents with decreasing polarity. Then, the ethyl acetate and petroleum ether extracts (EBP and PBP) were chosen to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(15 reference statements)
1
7
1
Order By: Relevance
“…Oral treatment of diabetic rats, in the current study, with hydroethanolic extracts of M. paradisiaca leaves and fruit peels significantly ameliorated serum glucose level. e observed decrease in the elevated glucose levels is in accordance with studies of Hongmei et al [46] who reported that the banana peel and its ingredient lupenone showed promising antihyperglycemic activity.…”
Section: Discussionsupporting
confidence: 91%
“…Oral treatment of diabetic rats, in the current study, with hydroethanolic extracts of M. paradisiaca leaves and fruit peels significantly ameliorated serum glucose level. e observed decrease in the elevated glucose levels is in accordance with studies of Hongmei et al [46] who reported that the banana peel and its ingredient lupenone showed promising antihyperglycemic activity.…”
Section: Discussionsupporting
confidence: 91%
“…More interestingly, based on the comparison of IC 50 values, lupenone has a marginally stronger (less than two times) α-glucosidase inhibitory activity than lupeol, while CE-one showed a significantly stronger inhibitory activity (more than 10 times) than CE-ol. It has been reported that lupenone in banana peel is a candidate possessing potent antidiabetic activity in alloxan-induced diabetic mice (Wu et al, 2015). However, our bioassay-guided fractionation did not identify lupenone in banana peel extract as an inhibitor of α-glucosidase and α-amylase.…”
Section: Identification Of Four Compounds From Banana Peel By Nmr Analysiscontrasting
confidence: 73%
“…The peel has been utilised in traditional medicine for the treatment of a range of ailments including burns, anaemia, diarrhoea, ulcers, inflammation, and excessive menstruation (Kumar et al 2012). Recent studies have reported various pharmacological properties of banana peel, such as inhibition against wide range of bacteria and fungi, reducing blood sugar, cholesterol and also inhibiting the development of some cancer cells (Pereira and Maraschin 2015;Sirajudin et al 2014;Wu et al 2015). In addition, banana peel exhibits strong antioxidant capacity (Singh et al 2016).…”
Section: Introductionmentioning
confidence: 99%